Non-uniqueness of fracture parameter choice in simulations of concrete cracking at mesoscale level - Kondys, B.; Bobiński, J.; Marzec, I. (Archives of Mechanics, 2023)
In the paper a non-uniqueness of fracture parameter choice in simulations of cracking process in plain concrete specimens at mesoscale level under monotonic static loading is analysed. The Finite Element Method is used, where cracks are defined in a discrete way using interface cohesive elements with nonlinear material law including softening. The concrete mesostructure (such as: cement matrix, air voids, aggregates, and Interfacial Transitions Zones (ITZ)) is taken into account. Two benchmarks: Montevideo splitting test (MVD) as a main test and the three-point beam bending test (TPBT) as an auxiliary problem are simulated. Results from 2D calculations are compared with experimental outcomes, especially force-crack opening curves and crack patterns are carefully studied. In the MVD test, the mesostructure of a specimen is taken from X-ray micro-computed tomography scans of real samples. The issue of the proper selection of material parameters for cohesive cracks is investigated. The ambiguity of such a process is presented and discussed. It turns out the numerical simulations can give the same outcome for different values of material parameters. The influence of the selected material parameters and the friction coefficient on results (force–crack opening curves and crack patterns) is also analysed.